Molecular diagnostics for detection and identification of Tilletia barclayana causing kernel smut of rice - Akhtar, Jameel; Tripathi, Aradhika; Celia Chalam, Vasimalla (The Indian Journal of Agricultural Sciences, 2026)
The cereal crop rice (Oryza sativa L.) is the staple food of over half of the world’s population. Rice kernel smut caused by fungal pathogen, Tilletia barclayana has become a challenging disease in rice-growing areas worldwide. The disease causes a significant yield loss during the rice production and also affects the seed quality. Keeping in view the importance of this pathogen of the most traded crop and non-availability of quick and reliable molecular detection protocol of the pathogen, the present study aimed to develop species-specific molecular markers for detection and identification of T. barclayana directly from seeds. Two sets of specific primers, TbarF2&R2 and TbarF2&R3 were developed from partial sequences of internal transcribed spacer (ITS) DNA region. Species-specific fragments of 308 bp was produced using TbarF2&R2 and 328 bp was amplified with the primer, TbarF2&R3 in T. barclayana. No amplification was obtained from the DNA of other Tilletia species and several other unrelated fungal plant pathogens tested in the present work indicating the specificity of the primers for the detection of the target pathogen. The specific primers detected the presence of T. barclayana in infected rice samples received for quarantine clearance from different countries. This quick PCR based diagnostic assay developed in the present study can be applied for the direct and rapid detection and identification of T. barclayana during quarantine processing and seed health testing to facilitate rice seed certification as well as quick quarantine clearance for international exchange of rice germplasm.